Congenital upper auricular detachment: Report of two unusual cases - Pawan Agarwal (Indian Journal of Plastic Surgery)
Two unusual cases of congenital bilateral ear deformity have been presented. The deformity is characterized by upper auricular detachment on the right side with anotia on the left side in the first case and upper auricular detachment on the left side with normal ear on the right side in the second case. An attempt has been made to correlate the presented deformity with the embryological – foetal development of the auricle. Satisfactory correction can be obtained by repositioning the auricle back in to its normal position.